2022
DOI: 10.1002/mds.29287
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers of Synaptic Dysfunction are Altered in Parkinson's Disease and Related Disorders

Abstract: A BS TRACT: Background: Synaptic dysfunction and degeneration are central contributors to the pathogenesis and progression of parkinsonian disorders. Therefore, identification and validation of biomarkers reflecting pathological synaptic alterations are greatly needed and could be used in prognostic assessment and to monitor treatment effects. Objective: To explore candidate biomarkers of synaptic dysfunction in Parkinson's disease (PD) and related disorders. Methods: Mass spectrometry was used to quantify 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Of special interest is that the levels seem to follow a constant linear decrease from controls to MCI and finally to AD ( 105 ). A similar pattern has also been found in PD ( 105 ), and the neuronal pentraxins seem to be potential monitoring biomarkers of the decline of cognitive and motor functions across neurodegenerative diseases; however, they seem to change later in the AD continuum than other synaptic biomarkers and possibly be more affected at later stages of AD ( 106 ).…”
Section: Synapse-associated Markerssupporting
confidence: 60%
See 2 more Smart Citations
“…Of special interest is that the levels seem to follow a constant linear decrease from controls to MCI and finally to AD ( 105 ). A similar pattern has also been found in PD ( 105 ), and the neuronal pentraxins seem to be potential monitoring biomarkers of the decline of cognitive and motor functions across neurodegenerative diseases; however, they seem to change later in the AD continuum than other synaptic biomarkers and possibly be more affected at later stages of AD ( 106 ).…”
Section: Synapse-associated Markerssupporting
confidence: 60%
“…Different members of the neuronal pentraxin family have been quantified in several SRM-based TMS assays and have commonly been found to have reduced CSF levels in AD in comparison with controls ( 106 ). Of special interest is that the levels seem to follow a constant linear decrease from controls to MCI and finally to AD ( 105 ).…”
Section: Synapse-associated Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few studies explored the relevance of neuronal pentraxins for PD pathology (Li et al, 2019; Moran et al, 2008). A couple of studies have recently reported decreased levels of NPTX1, NPTX2, and NPTXR in PD CSF (Lerche et al, 2021; Nilsson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We sought to ll this gap by investigating an established panel of lysosomal and synaptic markers (Table 2) validated in different cohorts [26][27][28] . Over a 10-year follow-up, we used this approach to longitudinally assess differently expressed proteins in CSF between subjects with iRBD, de novo PD, and healthy controls from our ongoing, prospective, single-center de novo Parkinson's disease (DeNoPa) cohort 29 .…”
Section: Introductionmentioning
confidence: 99%